(untitled) (Research, Society and Development, 2025)
Rudimentary septic systems are an alternative that serves the purpose of separating humans from their waste, preventing potential disease outbreaks, however, they also pose a potential source of groundwater contamination, particularly in areas where the water table is shallow, restricting the use of this water for human consumption without appropriate treatment. The present study aimed to analyze the water quality of shallow wells to identify possible contamination caused by the proximity of rudimentary septic systems in three wells (P1, P2, and P3) in São Gonçalo dos Campos, located in the Brazilian semi-arid region, during the dry and rainy seasons. It was observed that the septic systems did not maintain the minimum recommended distance of 45 meters from the wells, as specified by technical standards. This proximity between the two structures could result in contamination. Among the analyzed parameters, pH and salinity showed no significant variations in the wells between the sampled periods. However, for turbidity, Biochemical and Chemical Oxygen Demand, and Total Solids, there were notable changes in two wells (P1 and P3) across the analyzed periods, highlighting the influence of rainfall on these parameters. Regarding biological parameters (Escherichia coli and heterotrophic bacteria), a decrease in values was observed in all wells during the rainy season. Most of the parameters presented values above the limits established by legislation for potable water, indicating a possible relationship between alterations in physicochemical factors and contamination of the analyzed well water by the presence of rudimentary septic systems in nearby areas.